Firm Heterogeneity and Weak Intellectual Property Rights - Watt, Stanley (IMF Working Papers; Working Paper, 2007)
In weak intellectual property rights (IPR) environments, the imitation of proprietary technology by domestic firms has become a deterrent for foreign investment. Different multinationals may view this deterrent differently. This paper develops a model where firms with more technology are less likely to invest in weak IPR environments. If imitation is costly, the model predicts that multinationals with the lowest level and highest level of technology will invest in weak IPR environments, and multinationals with a moderate level of technology will invest only in strong IPR environments. Empirical analysis with firm level data is consistent with this non-monotonicity result.